Conflicts in Routing and UAV Autonomy: Algorithms for Ad-hoc & Infrastructure-based UAV Networks - Anicho, Ogbonnaya; Charlesworth, Philip B; Baicher, Gurvinder S; Nagar, Atulya (Journal of Telecommunications and the Digital Economy, 2018)
Routing is very fundamental to the implementation of any networking or communications infrastructure. This paper, therefore, examines the conflicts and relevant considerations for implementing autonomous or self-organising unmanned aerial vehicles (UAVs) for communications area coverage, with particular emphasis on the impact of aerial vehicle autonomy algorithms on routing techniques for such networks. UAV networks can be deployed either as ad-hoc or infrastructure-based solutions. The mobility of UAVs introduces periodic topology changes, impacting link availability and routing paths. This work examines the implications of autonomous coordination of multiple UAVs on routing techniques and network architecture stability. The paper proposes a solution where routing techniques and UAV autonomy algorithms are integrated for improved global network efficiency for both ad-hoc and infrastructure-based scenarios. Integrating UAV autonomy algorithms with routing schemes may be an efficient method to mitigate link/topology stability issues and improve inter-UAV communication and network throughput, a key requirement for UAV networks. The implementation of inter-UAV links using optical, microwave or mmWave transmission is examined in the context of this work. The proposed integration may be crucial for communications coverage, where UAVs provide communications area coverage of a community of mobile or fixed users in either ad-hoc or infrastructure-based modes.